Hubungan antara Ketidakhadiran dan Kepuasan Kerja Perawat Paviliun di RSD Jombang - Asmaningrum, Nurfika (Jurnal Keperawatan Soedirman, 2014)
Nursing service quality is determined by the nurses’ attitude themselves called job satisfaction that may affect morale. Absenteeism and turnover are expression of nurse job dissatisfaction. This observational study set cross-sectional design to identify relationship between nurse job satisfaction and work absenteeism. A questionnaire and observation were used. Sample is 20 nurses RSD Jombang selected by total sampling. Chi Square test was to test hypotheses. Results showed varies of job satisfactions level: fair (55%), lower (40%), and high (5%). Whilst, dimensions on nurse job satisfaction were group work and promotion (21.2%), salary (19.8%), employment (19.1%), and supervision (18.7%). Levels of absenteeism showed low (75%), and high (25%). There was weak correlation between nurses job satisfaction and absenteeism. Job satisfaction is not the only reason for nurses to absent in work, work absences causes were multifactors. It remains important for management to observe and manage the dimensional determinants of job satisfaction